2010
DOI: 10.3892/or_00000958
|View full text |Cite
|
Sign up to set email alerts
|

The role of common variants of non-homologous end-joining repair genes XRCC4, LIG4 and Ku80 in thyroid cancer risk

Abstract: Abstract. Variations, such as single nucleotide polymorphisms (SNPs) in DNA damage repair genes have been pointed out as possible factors to cancer predisposition. Ionizing radiation (IR) induces DNA double strand breaks (DSBs) and is the main recognized risk factor for thyroid cancer. However, most of the patients do not show chronic contact with IR and the other factors have non-concordant data. Thus, thyroid cancer could be due to gene variations in association with certain exogenous factors. One of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Twenty-four publications were included according to the established inclusion criteria. 13,32–54 A flow diagram of this process is shown in Figure 1. Subjects involved in the studies are not overlapping.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four publications were included according to the established inclusion criteria. 13,32–54 A flow diagram of this process is shown in Figure 1. Subjects involved in the studies are not overlapping.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of DNA ligase IV inhibitors for cancer sensitization to DNA damaging agents is poorly exploited (53). It has been shown that patients with homozygous mutations in DNA ligase IV are characterized by hyper-radiosensitivity (62)(63)(64). scRNAseq analysis showed reduced expression of the LIG4 gene at the mRNA level in normal follicular thyroid cells and thyroid cancer cells, but its activity is tightly regulated at the protein level by XRCC4 and DNA-PKcs (65).…”
Section: Discussionmentioning
confidence: 99%
“…No study showed a significant association between the tested polymorphisms and the risk of thyroid cancer. Gomes et al examined the rs1805377 (Asn298Ser) and rs28360135 (Thr134Ile) polymorphisms of XRCC4 and their interactions with LIG4 ; however, no significant gene-gene interaction was demonstrated, and the analysis of the polymorphisms did not indicate a relationship with the risk of cancer in the study population [ 53 ]. In the Arab population, the analysis of XRCC4 rs1805377 also did not show a significant statistical correlation with the risk of thyroid cancer compared to the control groups [ 29 ].…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%
“…XRCC5 / Ku80 gene polymorphisms have been investigated in the context of thyroid cancer. In the study by Gomes et al, the rs2440 polymorphism was not found to be significant in the overall Portuguese (Caucasian) population, but the logistic regression test showed significance for PTC but not for FTC (adjusted OR = 2.28; 95% CI = 1.06–4.89; p = 0.03) [ 53 ]. The remaining polymorphisms, that is, rs1051677, rs6941, and rs1051685, did not show statistically significant genotype differences between the study and control populations.…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%